Screening Test on Metabolic Syndrome Using Electro Interstitial Scan Instrument - Norchai P (Dove Medical Press, 2020)
Phawit Norchai,1 Thipaporn Tharavanij,2– 5 Picha Suwannahitatorn,6,7 Thammanard Charernboon1,8 1Department of Clinical Epidemiology, Faculty of Medicine, Thammasat University, Pathumthani, Thailand; 2Endocrinology and Metabolism Unit, Department of Medicine, Faculty of Medicine, Thammasat University, Pathumthani, Thailand; 3Diabetes and Metabolic Syndrome Research Unit, Faculty of Medicine, Thammasat University, Pathumthani, Thailand; 4Center of Excellence in Applied Epidemiology, Faculty of Medicine, Thammasat University, Pathumthani, Thailand; 5Thammasat University-Center of Excellence for Diabetic Foot Care, Thammasat University Hospital, Pathumthani, Thailand; 6Department of Parasitology, Phramongkutklao College of Medicine, Bangkok, Thailand; 7Biostatistics Unit, Office of Research Development Phramongkutklao Hospital and College of Medicine, Bangkok, Thailand; 8Department of Psychiatry, Faculty of Medicine, Thammasat University, Pathumthani, ThailandCorrespondence: Phawit NorchaiDepartment of Clinical Epidemiology, Faculty of Medicine, Thammasat University, 12120, ThailandTel +66 29269757Email dr.arkanay@gmail.comBackground: Metabolic syndrome is diagnosed using clinical and laboratory data. Electro interstitial scan (EIS) is a rapid and noninvasive screening. It measures and calculates the parameters to reflect hypertension, sympathetic activity, stiffness of the arteries, body fat composition, leptin and insulin resistance. Metabolic syndrome will be diagnosed if calculated score ≥ 10 CU.Purpose: To evaluate the accuracy, validity and appropriate cut-off score to diagnose metabolic syndrome.Materials and Methods: A cross-sectional study was conducted using the population-based approach. Metabolic syndrome was diagnosed according to the modified National Cholesterol Education Program (NCEP ATP III) and International Diabetes Federation (IDF) criteria. The appropriate cut-off score to diagnose metabolic syndrome by instrument was determined.Results: A total of 253 participants were enrolled with mean age of 40.06± 6.33 years, and 64.43% (163/253) were female. Metabolic syndrome was diagnosed among 123 (48.62%) and 104 (41.11%) patients according to the NCEP ATP III and IDF criteria, respectively. The diagnostic indices of metabolic syndrome score ≥ 10 CU had a sensitivity of 23.6% and 27.9%, a specificity of 100% and area under ROC of 0.62 and 0.64, according to the NCEP ATP III and IDF criteria, respectively. The best cut-off level of metabolic syndrome score was ≥ 9 CU with a sensitivity of 79.67% (95% CI, 71.5– 86.4%) and 88.46% (95% CI, 80.7– 93.9%), a specificity of 96.92% (95% CI, 92.3– 99.2%) and 93.29% (95% CI, 88.0– 96.7%) and area under ROC 0.89 (95% CI, 0.85– 0.93) and 0.92 (95% CI, 0.88– 0.95), respectively, according to the NCEP ATP III and IDF criteria.Conclusion: Screening of metabolic syndrome using ES TECK in a Thai population demonstrated inadequate accuracy when using metabolic syndrome score ≥ 10 CU. We recommend using a metabolic syndrome score ≥ 9 CU to provide the best accuracy. This instrument is safe, fast and easy to use for metabolic syndrome screening.Keywords: diagnostic, accuracy, validity, EIS, ES TECK